A Pandemia e a Igreja Católica no Brasil - Ferreira, Reuberson (Plura, revista de estudos de religião, 2021)
The purpose of this article is to point out the position that the Brazilian Episcopate, especially the archbishops, in different regions of the country has taken in relation to the pandemic of Invid-19. The proposal is to interpret how the archbishops, via official notes, reacted to the restrictions of agglomerations. What ways they took, what posture they took. At first, we will try to present the chronology of the documents write up by the archbishops trying to reveal to what extent the prelates heard the health recommendations and what were their decisions, for or against. In a second step, present the content of the notes and the arguments. Finally, list the disputes that were formed around episcopal decisions throughout the pandemic.